Excavation method in Goushfill mine - Cheraghi Seifabad, Masoud; Beheshti, Saeed (International Journal of Engineering and Technology, 2013)
This research tries to investigate the geomechanical parameters of rock mass in Goushfill mine. Using available cores, and studying existing methods, logs, and careful assessment of samples, four types of rock mass in Goushfill mine, shale, mineralized shale, dolomite and mineralized dolomite are classified, on the basis of GSI, RMR and Q-system. The physical parameters, friction angle and cohesion of rock mass are measured in the rock mechanics lab of Isfahan University of Technology. The excavation method is defined according to the results of the study and thus parameters of the excavation are specified.